Advances and future perspectives of neoadjuvant immunotherapy in colorectal cancer - ZHANG Yuyang, LIU Qian (Zhongguo aizheng zazhi)
In recent years, significant progress has been made in neoadjuvant immunotherapy for colorectal cancer (CRC), particularly demonstrating breakthrough efficacy in mismatch repair deficient/microsatellite instability-high (dMMR/MSI-H) subtypes. Immune checkpoint inhibitor (ICI) has achieved complete response (CR) rates as high as 41%-100% in this patient subgroup, driving the clinical adoption of “surgery-sparing” and “watch-and-wait” strategies. However, the majority of CRC patients with mismatch repair proficient/microsatellite stable (pMMR/MSS) tumors show limited response to ICI monotherapy, necessitating combination approaches with radiotherapy, chemotherapy, or targeted therapies to enhance efficacy. Current studies indicate that such combined regimens can elevate pathological complete response (pCR) rates to 22%-63%. Key research focuses include the synergistic effects of short-course radiotherapy (SCRT) combined with immunotherapy, the potential of dual-ICI therapy, and precision patient selection using biomarkers such as POLE/POLD1 mutations and tumor mutational burden (TMB). For treatment response assessment, the integration of colonoscopy, imaging, circulating tumor DNA (ctDNA) and artificial intelligence (AI) holds promise for optimizing clinical decision-making. Future efforts should prioritize immunomodulation strategies for pMMR/MSS patients, long-term safety evaluation of organ preservation approaches, and multidisciplinary collaboration to advance personalized therapy. Neoadjuvant immunotherapy is reshaping the CRC treatment paradigm, offering improved survival and quality of life for patients.